2016
DOI: 10.3390/pr4030021
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Punica granatum L. Juice Clarified by Hollow Fiber Membranes

Abstract: Abstract:There is currently much interest in pomegranate juice because of the high content of phenolic compounds. Moreover, the interest in the separation of bioactive compounds from natural sources has remarkably grown. In this work, for the first time, the Punica granatum L. (pomegranate) juice-clarified by using polyvinylidene fluoride (PVDF) and polysulfone (PSU) hollow fiber (HF) membranes prepared in the laboratory-was screened for its antioxidant properties by using different in vitro assays, namely 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
(46 reference statements)
3
5
0
Order By: Relevance
“…Herein, PVDF-clarified juice showed interesting in vitro antioxidant activity, as well as beta-glucosidase inhibitory activity, in comparison to the natural juice. These results are in agreement with data from our previous study [18] and from the work of Valero et al [26] that showed as clarification processes are able to produce positive effects on the antioxidant activity despite a reduction of phenols content of pomegranate juice. Indeed, we can deduce that the higher antioxidant effects of clarified juice could be explained through the removal of the antagonism between antioxidants and other constituents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Herein, PVDF-clarified juice showed interesting in vitro antioxidant activity, as well as beta-glucosidase inhibitory activity, in comparison to the natural juice. These results are in agreement with data from our previous study [18] and from the work of Valero et al [26] that showed as clarification processes are able to produce positive effects on the antioxidant activity despite a reduction of phenols content of pomegranate juice. Indeed, we can deduce that the higher antioxidant effects of clarified juice could be explained through the removal of the antagonism between antioxidants and other constituents.…”
Section: Discussionsupporting
confidence: 93%
“…The clarification of pomegranate juice with the PVDF membrane determined the highest protection on ROS production, according to our results obtained in vivo. This is consistent with phytochemical analysis that showed no significant retention of important antioxidant compounds in the MF juice [18], thus confirming the PVDF membrane as a useful tool for juice clarification with no negative effects on its biological activity. Moreover, the antioxidant activity of CJ seemed to be even higher than the NJ, thus suggesting that the filtration process may retain some compounds that limited such activity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…de Carvalho et al [28] evaluated the performance of different polymeric MF and UF In the selected operating conditions, polyvinylidene fluoride (PVDF) HF membranes showed higher initial (75 L/m 2 h) and steady-state (43.5 L/m 2 h) permeate fluxes in comparison to polysulphone (PS) membranes (initial permeate flux of 27 L/m 2 h and steady-state permeate flux of 4.8 L/m 2 h). A similar behavior was also observed in the clarification of pomegranate juice with PVDF and PS HF membranes [27]. The PVDF membranes presented, in fact, higher permeate fluxes in comparison with PS membranes.…”
Section: Clarification Of Aqueous Extract With Hollow Fiber Membranessupporting
confidence: 77%
“…Hollow fiber membranes in PVDF and PS, produced in laboratory, have been also tested for the clarification of pomegranate juice, in order to study the effect of membrane material on the functional properties of the clarified juice [37]. Experimental results indicated that PVDF membranes presented a lower retention towards healthy compounds, including flavonoids and anthocyanins, in comparison to PS membranes.…”
Section: Fruit Juice Clarificationmentioning
confidence: 99%